2022
DOI: 10.1097/med.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Imaging techniques to study diabetic bone disease

Abstract: Purpose of reviewThis review article presents the most recent research on bone fragility in individuals with diabetes from a medical imaging perspective.Recent findingsThe widespread availability of dual-energy X-ray absorptiometry (DXA) and trabecular bone score (TBS) software has led to recent assessments of bone fragility with this texture parameter in several studies of type 2 diabetes mellitus (T2D), but in few of type 1 diabetes mellitus (T1D). Although most studies show a trend of reduced TBS values in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Controversies remain as to whether or not BMD alone is sufficient to adequately assess BMD and predict osteoporotic fracture risk in PA. An interesting observation was the fact that plasma renin activity was inversely correlated with TBS only in females, but not in males, but BMD was not statistically significant different between PA cases and controls in both sexes according to one mentioned study [50]. As a lumbar DXA derivate, we mention that the use of TBS should be particularly encouraged in menopausal women with PA-related glucose profile anomalies [92,93].…”
Section: From Facts To Further Expansionmentioning
confidence: 76%
“…Controversies remain as to whether or not BMD alone is sufficient to adequately assess BMD and predict osteoporotic fracture risk in PA. An interesting observation was the fact that plasma renin activity was inversely correlated with TBS only in females, but not in males, but BMD was not statistically significant different between PA cases and controls in both sexes according to one mentioned study [50]. As a lumbar DXA derivate, we mention that the use of TBS should be particularly encouraged in menopausal women with PA-related glucose profile anomalies [92,93].…”
Section: From Facts To Further Expansionmentioning
confidence: 76%
“…However, it should be noted that these findings contrast with the data on BMD in type 1 diabetes mellitus (T1DM), in which BMD is typically lower than non-diabetic individuals, with T1DM being traditionally recognized as a cause of secondary osteoporosis with a 6.4-to 6.9-fold increase of fracture risk [84][85][86]. Concerning TBS, some authors showed that controlled T1DM is not correlated with a reduction of TBS [87], while others showed a decreased TBS in T1DM versus non-diabetic controls [88]; TBS was associated with prevalent fractures, but further studies are necessary to pinpoint the exact TBS cutoffs for fracture prediction in T1DM [89,90].…”
Section: Discussion 41 the Spectrum Of "Sweet Bones"mentioning
confidence: 99%
“…However, the benefit of QCT is that it represents a 3D imaging modality with the ability to differentiate trabecular and cortical bone compartments. Moreover, this imaging modality can generate volumetric bone mineral density assessments [7 ▪ ]. For fracture assessment, QCT can also be used for its ability to assess response of a structure such as bone to a mechanical load, a technique known as finite element analysis (FEA).…”
Section: Indirect Imaging Modalitiesmentioning
confidence: 99%